Upper mantle attenuation and velocity structure from measurements of differential S phases - Reid, F; Woodhouse, J; van Heijst, H (2001)
Although much progress has been made in determining the 3-D distribution of seismic wave velocities in the Earth, substantially less is known about the 3-D distribution of intrinsic attenuation. In this study variations in attenuation and shear velocity of the Earth's mantle are constrained using measurements of differential traveltime and attenuation. The data are broad-band displacement SH seismograms filtered to have energy in the period range 8-20 s. The seismograms are obtained from over 600 globally distributed earthquakes of magnitude, Mw, 5.5 or greater. Differential traveltimes and differential t* values from multiple S phases are estimated by a waveform-fitting method, resulting in approximately 4300 measurements for SS-S in the distance range 50°-105° and 1000 measurements for SSS-SS in the distance range 90°-179°. Each measurement consists of a differential traveltime and a corresponding differential t*. The differential traveltimes and t* values are inverted to obtain models of the lateral variation of shear velocity and lateral variation of qμ, where qμ = 1/Qμ. The models explain the data well but have limited depth resolution. The velocity models show good correlation with previous studies; in particular, low velocities are observed underlying mid-oceanic ridges and convergent margins and high velocities are found for continental regions. The Qμ models show shield regions to be less attenuating than PREM, with ridges appearing as highly attenuating features. The models have limited depth resolution and to address this problem we also present a shear velocity model obtained from the combination of body wave and surface wave data sets.